On the demonstration of the normal polarity of remanent magnetization by volcanic rocks containing magnetite or hematite - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2010)
Magnetic and paleomagnetic properties, and magnetic mineralogy of the Neogene andesitic rocks were previously studied. The author of the article has recently proposed a model of the sources of normal and reversed RM and tested it applying the results of the submarine volcanics (Orlický, 2010). The magnetites (cubic phase) and the titanium rich titanomagnetites (cubic phase) have been considered as the carriers of only normal remanent magnetization of the rocks. The low-temperature oxidized titanomagnetites and the Ilmenite-Hematites (Ilm-Hem; rhombohedral phase) carry either the reversed remanent magnetism (RM) of self-reversed origin, or normal RM, depending on the proportion of hematite in the Ilm-Hem solid solutions. I have enlarged the original model in the hematite bearing rocks which carry only normal RM. The paleomagnetic and magnetic results and the results of magnetic mineralogy of selected Neogene andesites and rhyolites from central, southern and eastern Slovakia of the Badenian to the Middle or Lower Sarmatian age (16.05–12.9 M.Y.) have been considered. The selected rocks with the magnetites and hematites have revealed only the normal RM. Normal partial thermoremanent magnetization (PTRM) was induced in many magnetites and hematites containing andesite and rhyolite samples in the laboratory. The occurrence of both these types of magnetic minerals is quite rare in volcanics. While the magnetite is more frequently present in the intrusive rocks, the hematite is frequently present in effusive, more acidic volcanics, e.g. in the rhyolites. Very important outcome is that both magnetite and hematite are the carriers of only normal polarity of RM in the rocks, regardless their age.